Extremely Preterm Infant Admissions Within the SafeBoosC-III Consortium During the COVID-19 Lockdown - Rasmussen, Marie Isabel; Hansen, Mathias Lühr; Pichler, Gerhard; Dempsey, Eugene; Pellicer, Adelina; EL-Khuffash, Afif; A, Shashidhar; Piris-Borregas, Salvador; Alsina, Miguel; Cetinkaya, Merih; Chalak, Lina; Özkan, Hilal; et al. (Frontiers in Pediatrics, 2021)
Objective: To evaluate if the number of admitted extremely preterm (EP) infants (born before 28 weeks of gestational age) differed in the neonatal intensive care units (NICUs) of the SafeBoosC-III consortium during the global lockdown when compared to the corresponding time period in 2019. Design: This is a retrospective, observational study. Forty-six out of 79 NICUs (58%) from 17 countries participated. Principal investigators were asked to report the following information: 1) Total number of EP infant admissions to their NICU in the three months where the lockdown restrictions were most rigorous during the first phase of the COVID-19 pandemic, 2) Similar EP infant admissions in the corresponding three months of 2019, 3) the level of local restrictions during the lockdown period and 4) the local impact of the COVID-19 lockdown on the everyday life of a pregnant woman. Results: The number of EP infant admissions during the first wave of the COVID-19 pandemic was 428 compared to 457 in the corresponding three months in 2019 (- 6.6%, 95% CI -18.2 to + 7.1%, p=0.33). There were no statistically significant differences within individual geographic regions and no significant association between the level of lockdown restrictions and difference in the number of EP infant admissions. A post hoc analysis based on data from the 46 NICUs found a decrease of 10.3% in the total number of NICU admissions (n=7499 in 2020 vs n=8362 in 2019). Conclusion: This ad hoc study did not confirm previous reports of a major reduction in the number of extremely preterm births during the first phase of the COVID-19 pandemic.